Household Accounting Values and Implementation Interpretive Study - Arief Prima Raharjo; Ari Kamayanti (The Indonesian Journal of Accounting Research, 2015)
Abstract: This research aims to explain the implementation of household accounting in a conjugal family and extended family owning micro-scale businesses using interpretive paradigm. The results of this research suggest that values existing in household accounting practice such as trustworthiness and religious (not redundant, halal) values become the bases of the practice of household accounting. In a conjugal family owning micro scale business, household accounting is implemented separately from business accounts. In an extended family owning micro scale business, household accounting is kept as one record with a business record. Another interesting finding is that wives are trusted by husbands to manage household decision for disposable and small nominal goods like household appliances, and vegetables. For products with significant nominal sum and long-term economic age like a refrigerator, motorcycle, and car, it is the husbands who are involved in decision making. Abstrak: Tujuan dari penelitian ini adalah untuk menjelaskan implementasi akuntansi rumah tangga pada keluarga conjugal dan keluarga extended yang memiliki bisnis berskala mikro menggunakan paradigma interpretif. Hasil penelitian ini adalah nilai-nilai yang muncul pada praktek akuntansi rumah tangga seperti nilai kepercayaan dan religius (tidak mubazir, halal) menjadi dasar dari praktik akuntansi rumah tangga. Pada keluaga conjugal yang memiliki bisnis berskala mikro, akuntansi rumah tangga diimplementasikan terpisah dari akuntansi bisnis. Pada keluarga extended yang memiliki bisnis berskala mikro, akuntansi rumah tangga dijadikan satu dengan akuntansi bisnis. Temuan menarik lainnya adalah istri dipercaya oleh suami untuk mengelola keputusan dalam rumah tangga untuk barang sekali pakai dan barang bernominal kecil seperti peralatan rumah tangga dan sayur mayur. Untuk barang dengan nominal besar dan memiliki umur ekonomis yang panjang seperti kulkas, sepeda motor, dan mobil, suami ikut terlibat dalam pengambilan keputusan.